Prioritizing Learning Topics of Coding Curriculum for Elementary Students Using the Analytic Hierarchy Process - Lim, Dongkyun; Eun Lee, Ji; Moon, Dosik; Um, Gijun (International Journal of Engineering and Technology, 2018)
As the world confronts the 4th industrial revolution era, there is a growing interest in coding education around the world to cultivate creative and convergent students who possess computational thinking and problem-solving skills. In order for coding education to be successful, the following questions are considered: 1.What should be taught first? 2. How should it be taught? This study aims to determine the priority of leaning topics in elementary school coding education. To do so, a focus group interview was conducted with four experts in the field of coding education, and 12 learning topics were identified. Based on the interview results, a questionnaire was administered to coding instructors. The Analytic Hierarchy Process (AHP) was applied to derive priorities among the learning topics. The results showed that â€˜procedural problem solvingâ€™ was found as the most important unit that the elementary school coding education needs to deal with. As for the learning topics, â€˜problem definition and breakdownâ€™, â€˜block codingâ€™, â€˜implementation of algorithmâ€™, â€˜understanding of algorithmâ€™ and â€˜necessity for learning codingâ€™ were found to be the top 5 priorities. Based on these results, this study presents four suggestions to consider for coding education to be carried out more effectively.Â Â